Perencanaan lanskap Villa Cloud Nine Estate dengan pendekatan permakultur di Kecamatan Tegallalang, Kabupaten Gianyar, Bali - Wardhani, Atria; Gunadi, I Gusti Alit; Kohdrata, Naniek (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020DO - 10.24843/JAL.2020.v06.i01.p02, 2020)
Villa Cloud Nine Estate is one of the tourism accommodations that cares about environmental problems in Bali. This villa has the potential for permaculture planning. A permaculture is a place that can be used for the management of agriculture and livestock to improve the quality of land, provide results and income, and remain sustainable into the future. This study aims to determine the condition of the site and its potential so as to produce a landscape plan that fits the characteristics of the villa landscape. The stages of this research are preparation, inventory, analysis, synthesis and site planning. The results of the data analysis show that the site has low land characteristics with high rainfall throughout the year. The character of the landscape on the site is natural with the main landscape elements in the form of grass and trees. The basic concept produced in this study is The Journey of Permaculture. Landscape planning is designed based on the concept of space, the concept of circulation, the concept of vegetation, and the concept of hydrology. The layout is divided to create zones that can save the time and effort needed. The vegetation is divided into production plants, conservation plants and supporting plants. Villa Cloud Nine Estate is one of the tourist accommodations that applies permaculture on the site.